Human Resource Management - syahril (Nusantara: Journal of Cultural Research, 2024)
This article aims to discuss the importance of Human Resource Management (HRM) in achieving organizational goals, especially in the corporate context. The type of research used is literature study by collecting data from primary sources such as books and journal articles. The data collection technique in this library study research is by browsing and reading various literature or written sources related to the research. The analysis technique used in this research is descriptive analysis through stages including identifying the research topic and focus, collecting literature and related sources, grouping information from the literature, presenting data systematically, understanding the context, and drawing conclusions. HRM includes planning, organizing, directing and monitoring processes designed to maximize workforce potential. The main focus includes providing, training and developing human resources, as well as providing care and maintenance of the workforce. The recruitment, training and HR development process is explained as a strategic step to improve the quality of the workforce in order to meet company targets. In addition, giving rewards and maintaining employees is stated as a way to maintain motivation, loyalty and productivity. With this approach, this paper emphasizes that effective and efficient human resource management is the key to organizational success in a dynamic environment